DAYA TERIMA BAKSO BELUT SAWAH DAN KACANG KEDELAI: SUMBER FE DAN KALSIUM - Mannan, Muthia Muthmainnah; Salam, Abdul; Marini Amalia Mansur; Zainal; Safrullah Amir (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2023)
Introduction: Dysmenorrhea in early adult women can be overcome by consuming food sources of iron and calcium, such as eel and soybeans. Objectives: This study aims to determine the production process and the acceptability of meatballs based on eel and soybeans. Methods: This study used a descriptive observational design. The semi-trained panelists consisted of 11 lecturers and staff from the Hasanuddin University School of Public Health for the hedonic quality test and the consumer panelists consisted of 65 undergraduate students of Public Health Faculty of Public Health Hasanuddin University for the hedonic (preference) test who belonged to the early adult group. The research was divided into preliminary research stages (making meatball products) and main research (hedonic quality tests and hedonic tests) using questionnaire research instruments. Results: The composition of the ratio of paddy eel and soybeans is a ratio of 100:15 for formula 2 (F2) or 22%, 100:20 for formula 3 (F3) or 33%, 100:25 for formula 4 (F4) or 45% and control formula (F1) which only uses paddy eel as the main ingredient. The results of the hedonic quality test by semi-trained panelists who had the highest score overall were formula 2. The most preferred consumer panelist test results for each parameter were color parameter F4 (72%), aroma parameter F2 (69.2%), taste parameter FI (72.3%) and texture parameters F1 (68.9%). Overall the most preferred formula with the highest acceptance rate is F2 (66.23%). Conclusion: Based on the results of the organoleptic test as a whole the most preferred formula is F2, to improve the taste in the manufacturing process, soybeans are soaked first and then exfoliated on the skin to minimize the bitter and sepet taste.